Effect of vitamin D deficiency on clinical pregnancy outcomes in women with polycystic ovary syndrome undergoing in vitro fertilization - Yu, Lan; Hu, Bin; Kong, Jing; Xu, Xiaohang; Zhang, Cuilian (Frontiers in Endocrinology, 2025)
PurposeThis study aimed to investigate the effect of serum vitamin D levels on in vitro fertilization and embryo transfer (IVF-ET) in patients with polycystic ovary syndrome (PCOS).MethodsThis retrospective cohort study included patients with PCOS who underwent IVF therapy and received fresh embryo transfer for the first time. The enrolled cohort was divided into two groups based on serum 25-hydroxyvitamin D (25(OH)D) levels: Vitamin D deficiency (25(OH)D < 20 ng/mL) and vitamin D replete-insufficiency (25(OH)D ≥ 20 ng/mL). The primary outcome was clinical pregnancy. The secondary outcomes were the number of oocytes retrieved, MII oocytes, fertilized embryos, available embryos, high-quality embryos, blastocysts formed, and live birth rates.ResultsThis study included 613 patients who underwent their first IVF-ET cycle. Clinical pregnancy rates were significantly lower in patients with PCOS who had vitamin D deficiency than in those who had vitamin D replete-insufficiency [58.3% (211/367) versus 67.1% (163/246); P = 0.029]. Logistic regression, adjusted for endometrial thickness, progesterone, and vitamin D levels, demonstrated that serum vitamin D ≥ 20 ng/mL was independently associated with higher clinical pregnancy rates than the vitamin D deficiency group (odds ratio 1.48; 95% confidence interval, 1.02–2.32; P = 0.032). However, vitamin D deficiency did not significantly affect live birth rates (P = 0.57). We found no significant differences in the number of oocytes, MII oocytes, fertilized embryos, and the percentage of top-quality embryos between the two groups.ConclusionThis study suggests that vitamin D deficiency leads to lower clinical pregnancy rates in patients with PCOS undergoing IVF-ET. Furthermore, the serum vitamin D level is independently associated with clinical pregnancy rates in patients with PCOS undergoing IVF-ET.